(untitled) (Innovation & Development in Engineering and Applied Science, 2025)
The article analyzes the influence of injection frequency and timing on the performance of electronic injectors. In the experimental process, two independent variables and three dependent variables were controlled, obtaining the amount of delivery, fuel return, and rail pressure using injection pulse simulation equipment. Tests were carried out with different combinations of time and frequency. The results showed that frequency has a significant influence on the amount of injection and fuel return, being the most relevant variable. It was found that fuel delivery increases as a function of time and frequency, with 1.5 ms being the point where the highest delivery was obtained when varying from 5 to 20 Hz. In addition, the rail pressure showed an inverse relationship with injection time and frequency, decreasing by 17.5%, 11.1%, 11.4%, and 11.7% at values of 5, 10, 15, and 20 Hz, respectively. Statistical analysis revealed that the adjusted models effectively explain the variability in fuel delivery and rail pressure.